PENGGUNAAN BIBIT KARET UNGGUL OLEH PETANI KARET DI JAMBI DAN KALIMANTAN BARAT; MOTIVASI DAN HAMBATAN - iskandar, dudi (Jurnal Sains dan Teknologi Indonesia, 2011)
The contribution of rubber to national economic and social development is important for Indonesia. However, smallholding rubber, the dominant rubber producer, has low productivity. Indonesian government has been introduced various technologies including clonal planting material to increase the productivity increase rubber production and farmers’ incomes. However. This study helped to identify the main reasons, motivations and constraints that influenced a farmer’s decision in Jambi and West Kalimantan to adopt or not adopt clonal rubber by using Focus GroupDiscussion (FGD) method. This study show that the main constraint in adoption for both areas was limitation of capital as the clonal rubber required more capital to establish. The other constraints are risk and uncertainties including pest and disease problems, the shortage of labour, lack of access to clonal seedlings. This study result can be used by Indonesian Government in order to encourage rubber farmers inJambi and West Kalimantan to adopt clonal rubber to increase rubber productivity as well as farmer’s income.